LEARNING THE QURAN HADITH WITH THE MIND MAP METHOD TO IMPROVE STUDENT LEARNING OUTCOMES - Zarkasi, Zarkasi (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
This study intends to improve the student's learning outcomes of Al-Qur'an Hadith subjects in class XII-IPA 1 at MAS Miftahussalam Demak by using the mind mapping method. The approach used in this research is Classroom Action Research (CAR) using Kurt Lewin's research model which consists of four stages: Planning, Implementation, Observation, and Reflection. Based on the results of the study, it was concluded that the use of the mind mapping method could improve student learning outcomes in the subjects of Al-Qur'an Hadith, the subject of preserving the environment. This can be seen from the data on student learning outcomes in the first cycle which initially only 44% (seven) of students have achieved the desired competence according to the Minimum Completeness Criteria (KKM) from their learning outcomes, while 56% (nine) students have not achieved Minimum Completeness Criteria. Then in cycle II, the learning outcomes of students increased by 81%, namely 13 students whose scores were above the KKM, while there were still three more students who had not reached the Minimum Completeness Criteria. In cycle III the increase in student learning outcomes finally achieved very satisfying results, namely 100% passing the KKM and there were four students whose scores reached 100 and the scores of other students experienced a very satisfying increase.